176 A Histone Deacetylase 7-Derived 7 Amino Acid Peptide Acts as a Phosphorylation Carrier. (3rd June 2016) - Yang, Junyao; Lao, Ka Hou; Zeng, Lingfang
Abstract : Histone deacetylase 7 (HDAC7) belongs to class II HDAC family, playing a pivotal role in the maintenance of endothelium integrity. There are 8 splicing variants in mouse HDAC7 mRNAs. Within the 5â€™ terminal non-coding area of some variants, there exist some short open reading frames (sORFs). Whether these sORFs can be translated and their potential roles in cellular physiology remain unclear. In this study, we demonstrated that one sORF encoding a 7 amino acids (aa)-peptide could be translated in vascular progenitor cells (VPCs) in response to vascular endothelial cell growth factor (VEGF). The 7aa-peptide (7A) could be phosphorylated at serine residue via MEKK1. Importantly, the phosphorylated 7A (7Ap) could transfer the phosphorylation group to the Threonine residue of the 14–3–3Î³ protein in a cell free in-gel buffer system. The in vitro functional analyses revealed that 7A enhanced VEGF-induced VPC migration and differentiation toward endothelial cell (EC) lineage, in which MEKK1 and 14–3–3Î³ served as the upstream kinase and the downstream effector respectively. Knockdown of either MEKK1 or 14–3–3Î³ attenuated VEGF-induced VPC migration and differentiation. Exogenous 7Ap could rescue the effect of VEGF on the MEKK1 siRNA-transfected but not on the 14–3–3Î³ siRNA-transfected VPCs. The in vivo studies showed that 7A especially 7Ap induced capillary vessel formation within Matrigel plug assays, increased re-endothelialization and suppressed neointima formation in the femoral artery injury model, and promoted the foot blood perfusion recovery in the hindlimb ischemia model via increasing Sca1 + cell niche formation. These results indicate that the sORFs within the non-coding area can be translated under some circumstances and that the 7aa-peptide may play an important role in cellular processes like migration and differentiation via acting as a phosphorylation carrier.